2021
DOI: 10.1111/pcmr.12999
|View full text |Cite
|
Sign up to set email alerts
|

Acral lentiginous melanoma—Population, treatment, and survival using the NCDB from 2004 to 2015

Abstract: Acral lentiginous melanoma (ALM) is a rare histological subtype of melanoma, accounting for 1%-3% of cutaneous malignant melanomas (CMM) (Bradford et al., 2009;Huang et al., 2020). It was first described by Reed in 1976 as a "distinct clinicopathologic entity… pigmented lesions on the extremities, particularly on plantar regions, like the palms of the hands and soles of the feet" (Reed, 1976). The anatomic descriptor "acral" means extremity while "lentiginous" describes the histologic side-by-side arrangement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…Some studies conducted on the white race reported a clear prevalence of ALM in females. 11,12 However, our study did not find any significant differences in gender predominance, which is consistent with the majority of previous research. 13…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some studies conducted on the white race reported a clear prevalence of ALM in females. 11,12 However, our study did not find any significant differences in gender predominance, which is consistent with the majority of previous research. 13…”
Section: Discussionsupporting
confidence: 93%
“…Some studies conducted on the white race reported a clear prevalence of ALM in females. 11,12 However, our study did not find any significant differences in gender predominance, which is consistent with the majority of previous research. 13 Most authors believe that the average age at diagnosis of ALM is higher compared to other melanoma types, primarily due to postprognosis and misdiagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found the relationship between high expression of Ki-67 and melanoma thickness. Thus, the previous findings of the correlations of Ki-67 expression and tomor size in various solid cancers are in accordance with the present study.A recent study showed that melanoma tumor thickness is strongly associated with poor 5-year OS (33). Therefore, the high expression of KI-67 indicates the poor prognosis of melanoma patients, which may be related to tumor thickness.…”
Section: Discussionmentioning
confidence: 99%
“…42 Acral lentiginous melanoma has an unclear etiology thought to be distinct among CMMs, with hypothesized environmental factors including trauma and chemical exposures. [43][44][45][46] Given the unique mutational landscape of ALM tumors, with their much lower incidence of BRAF mutations and increased incidence of KIT and CDK gene mutations compared with UV-related CMMs, ALM may have a particular proclivity toward nonstepwise regional metastasis. [15][16][17][18] This has notable implications for using traditional histopathologic adverse features in the diagnostic and treatment algorithm for ALM.…”
Section: Discussionmentioning
confidence: 99%
“…This has notable implications for using traditional histopathologic adverse features in the diagnostic and treatment algorithm for ALM. An alternative hypothesis for this association is that, owing to ALM's relatively high rate of resection with positive margins, reported Breslow depths may underestimate the true invasiveness of such tumors …”
Section: Discussionmentioning
confidence: 99%